(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The hours of the day are twenty-four (24) hours, and each hour among the Arabs has a name. Al-Tha’alibi mentioned the names of the hours of the day in his book (Fiqh al-Lughah), entitled: A Chapter on the Enumeration of the Names of the Hours of the Day and Night in Twenty-Four Words. This study aimed to trace the names of the hours of the day and night among the Arabs and shed light on them linguistically. The study relied on the analytical inductive approach, a lexical, morphological, and semantic study. The researcher developed the idea of ​​studying the names of the hours of the day and night among the Arabs linguistically, with an introduction of two sections. The first section, which studies the names of the hours of the night, contains twelve sections. The second section, which studies the names of the hours of the day, contains twelve sections. The conclusion includes the results and a list of sources and references.